2019
DOI: 10.22437/jiiip.v22i2.6725
|View full text |Cite
|
Sign up to set email alerts
|

Efisiensi Protein Ayam Broiler yang Diberi Ampas Tahu Fermentasi dengan Saccharomyces cerevisiae (Protein Efficiency of Broiler Chicken Fed fermented Waste Tofu with Saccharomyces cerevisiae)

Abstract: Tujuan dari penelitian ini adalah untuk mengevaluasi pertambahan bobot badan dan efisiensi penggunaan protein pada ayam broiler yang diberi pakan mengandung  ampas tahu hasil fermentasi menggunakan Saccaromyces cerevisae. Ampas tahu difermentasi menggunakan Saccharomyces cerevisiae sebanyak 2 % dengan lama waktu fermentasi 72 jam. Setelah dipanen dianalisa kandungan nutrisinya dan diberikan pada ayam broiler sebanyak 200 ekor selama 5 minggu pemeliharaan. Rancangan yang digunakan adalah Rancangan Acak Lengkap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
5
0
7
Order By: Relevance
“…According to Saferi et al (2005), enzymes produced by YC can break down complex carbohydrates, such as cellulose, hemi sulolsa, and lignin, and can increase the availability of the amino acid lysine. Nurhayati et al (2019) reported that the protein content of tofu waste increased 15.30% higher than the control (without fermentation) when fermented with 5% Trichoderma viride and increased by 15.80% when fermented with 2% Saccharomyces cerevise, on the other hand, the EE content decreased. The extracellular enzyme activity of YC in increasing the nutritional value of feed is by: (i) producing hydrolase enzymes that break down the cellulose and hemicellulose fractions, and (ii) secreting extracellular lignase enzymes by depolymerizing lignin (Perez et al 2002).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…According to Saferi et al (2005), enzymes produced by YC can break down complex carbohydrates, such as cellulose, hemi sulolsa, and lignin, and can increase the availability of the amino acid lysine. Nurhayati et al (2019) reported that the protein content of tofu waste increased 15.30% higher than the control (without fermentation) when fermented with 5% Trichoderma viride and increased by 15.80% when fermented with 2% Saccharomyces cerevise, on the other hand, the EE content decreased. The extracellular enzyme activity of YC in increasing the nutritional value of feed is by: (i) producing hydrolase enzymes that break down the cellulose and hemicellulose fractions, and (ii) secreting extracellular lignase enzymes by depolymerizing lignin (Perez et al 2002).…”
Section: Discussionmentioning
confidence: 96%
“…The extracellular enzyme activity of YC in increasing the nutritional value of feed is by: (i) producing hydrolase enzymes that break down the cellulose and hemicellulose fractions, and (ii) secreting extracellular lignase enzymes by depolymerizing lignin (Perez et al 2002). Reported by Nurhayati et al (2019) that the crude fiber content of tofu waste decreased by 13.08% when fermented with Trichoderma viride and did not show any difference when fermented with S. cerevise compared to controls. The content of BC in tofu waste is low, whereas in carrots it is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichoderma viride can increase the protein content of shrimp waste to 41.27% with protein digestibility of 81.24% [18] Trichoderma sp. has two types of extracellular enzyme work systems, as follows: (1) hydrolytic system, namely by producing hydrolase enzymes that work to break down cellulose and hemicellulose, and (2) oxidative system and extracellular lignase secretion by depolymerizing lignin [19,20]. The survival rate of Asian sea bass during the study which was fed with the percentage of fish meal substitution with fermented shrimp shell meal showed significantly different results.…”
Section: Discussionmentioning
confidence: 99%
“…Enzim-enzim yang dihasilkan oleh mikrorganisme pada proses fermentasi dapat meningkatkan kualitas bahan pakan yang difermetasi, khususnya bahan pakan yang mengandung serat kasar dan zat antinutrisi yang tinggi karena terjadi penyederhanaan zat-zat yang terkandung dalam bahan pakan tesebut (Nurhayati et al, 2020). Selain itu (Kanti, 2017) melaporkan bahwa enzim fitase dan amilase bisa dihasilkan dari ampas tahu yang difermentasi dengan menggunakan oleh kapang R. oryzae, A. niger dan Neurospora sitophila.…”
Section: Hasil Dan Pembahasanunclassified